Successional Dynamics and Seascape-Level Patterns of Microbial Communities on the Canopy-Forming Kelps Nereocystis luetkeana and Macrocystis pyrifera - Weigel, Brooke L.; Pfister, Catherine A. (Frontiers in Microbiology, 2019)
Canopy-forming kelps create underwater forests that are among the most productive marine ecosystems. On the Pacific coast of North America, two canopy-forming kelps with contrasting life histories co-occur; Macrocystis pyrifera, a perennial species, and Nereocystis luetkeana, an annual species. Kelp blade-associated microbes were sampled from 12 locations across a spatial gradient in Washington, USA, from the outer Pacific Coast to Puget Sound. Microbial communities were characterized using next-generation Illumina sequencing of 16S rRNA genes. At higher taxonomic levels (bacterial phylum and class), canopy-forming kelps hosted remarkably similar microbial communities, but at the amplicon sequence variant (ASV) level, microbial communities on M. pyrifera and N. luetkeana were host-specific and distinct from free-living bacteria in the surrounding seawater. Microbial communities associated with blades of each kelp species displayed significant geographic variation. The microbiome of N. luetkeana changed along the spatial gradient and was significantly correlated to salinity, with outer Pacific coast sites enriched in Bacteroidetes (family Saprospiraceae) and Gammaproteobacteria (Granulosicoccus sp.), and southern Puget Sound sites enriched in Alphaproteobacteria (family Hyphomonadaceae). We also examined microbial community development and succession on meristematic and apical N. luetkeana blade tissues throughout the summer growing season on Tatoosh Island, WA. Across all dates, microbial communities were less diverse on younger, meristematic blade tissue compared to the older, apical tissues. In addition, phylogenetic relatedness among microbial taxa increased from meristematic to apical blade tissues, suggesting that the addition of microbial taxa to the community was a non-random process that selected for certain phylogenetic groups of microbes. Microbial communities on older, apical tissues displayed significant temporal variation throughout the summer and microbial taxa that were differentially abundant over time displayed clear patterns of community succession. Overall, we report that host species identity, geographic location, and blade tissue age shape the microbial communities on canopy-forming kelps.